SODIUM INTAKE, LIFE EXPECTANCY AND ALL-CAUSE MORTALITY. (April 2021) - Messerli, Franz; Hoftetter, Louis; Syrogiannouli, Lamprini; Rexhaj, Emrush; Siontis, George; Seiler, Christian; Bangalore, Sripal
Abstract : Objective: Since dietary sodium intake has been identified as a risk factor for cardiovascular disease and premature death, a high dietary sodium intake can be expected to curtail life span. We tested this hypothesis by analyzing the relationship between sodium intake and life expectancy as well as survival in 181 countries worldwide. Design and method: We correlated age-standardized estimates of country specific average sodium consumption with healthy life expectancy at birth and at age of 60 years, and all-cause mortality for the year of 2010, after adjusting for potential confounders such as gross domestic product per capita and body mass index. We considered global health estimates as provided by World Health Organization. Results: Among the 181 countries included in this analysis, we found a positive correlation between sodium intake and healthy life expectancy at birth (R2 = 0.661, p < 0.001), as well as healthy life expectancy at age 60 (R2 = 0.600, p = 0.048). Conversely, all-cause mortality correlated inversely with sodium intake (R2 = 0.597, p < 0.001), Figure 1. In a sensitivity analysis restricted to 46 countries in the highest income class, sodium intake continued to correlate positively with healthy life expectancy at birth (R2 = 0.533, p < 0.001) and inversely with all-cause mortality (R2 = 0.497, p < 0.001). Figure. No caption available. Figure 1: Relation of sodium intake (grams/day) for the year of 2010 and healthy life expectancy at birth (in years) and age-standardized death rates (ASDR) for all-cause mortality in 181 countries worldwide. Schematic pattern of change in life expectancy and all-cause mortality with sodium intake in 181 countries worldwide. Note that proposed upper limits by some organizations such as AHA, WHO and ESC are associated with rather low life expectancy and high mortality. Conclusions: Our observation of sodium intake correlating positively with life expectancy and inversely with all-cause mortality worldwide and in high income countries argues against dietary sodium intake being a culprit of curtailing life span or a risk factor for premature death. These data are observational and should not be used as a base for nutritional interventions.